Postoperative systemic inflammatory response syndrome predicts increased mortality in patients after elective craniotomy - Peng, Liyuan; Gan, Qi; Xiao, Yangchun; He, Jialing; Cheng, Xin; Wang, Peng; Chen, Lvlin; Li, Tiangui; He, Yan; Chong, Weelic; Hai, Yang; You, Chao; et al. (Frontiers in Surgery, 2024)
Patients undergoing craniotomy are at high risk of perioperative morbidity and mortality due to the excessive inflammatory response. The purpose of our study is to evaluate the prognostic utility of postoperative systemic inflammatory response syndrome (SIRS) in patients undergoing craniotomy.We performed a retrospective cohort study of patients undergoing craniotomy between January 2011 and March 2021. The diagnosis of SIRS was based on two or more criteria (hypo-/hyperthermia, tachypnea, leukopenia/leukocytosis, tachycardia). Using univariate and multivariate analysis for the development of SIRS with postoperative 30-day mortality.Of 12887 patients underwent craniotomy, more than half of the patients (n = 6725; 52.2%) developed SIRS within the first 7 days after the surgery and 157 (1.22%) patients died within 30 days after the surgery. In multivariable analyses, SIRS (OR, 1.57; 95% CI, 1.12-2.21) were associated with 30-day mortality. Early SIRS was not predictive of 30-day mortality; by contrast, delayed SIRS was predictive of 30-day mortality. It was abnormal WBC counts that contributed most to the SIRS score, followed by abnormal body temperature, respiratory rate, and heart rate.Postoperative SIRS occur commonly after craniotomy and is an independent predictor of postoperative 30-day mortality. This association was only seen in delayed SIRS but not early SIRS.Moreover, increased WBC counts contributed the most to the SIRS score.